“PENGARUH PROFITABILITAS, KEPEMILIKAN INSTITUSIONAL TERHADAP KEBIJAKAN DIVIDEN DENGAN LIKUIDITAS SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2016” - Dewi Yuliani, 14.05.52.0179; Suwarti, Titiek (Students' Journal of Accounting and Banking, 2018)
This study aims to test profitability, institutional ownership and liquidity as a moderating variable to dividend policy. This research is conducted in Indonesia by using unit analysis of manufacturing companies that have go-public. The population of this study is a manufacturing company listed on the stock exchange Indonesia. Sampling method using purposive sampling with period of research year 2014 until 2016 and obtained by 34 company. The technique of data analysis used is multiple linier regression analysis. The results showed that profitability has a significant positive effect on dividend policy, institutional ownership has no significant negative effect on dividend policy, liquidity as a moderating variable affects the profitability of dividend policy having negative effect is not significant and liquidity as a moderating variable affects institutional ownership of dividend policy having a non significant positive effectKeyword: Profitability, Institutional Ownership, Liquidity and Dividend Policy